Value at risk como medida de risco da volatilidade dos ajustes diários em mercados futuros de café - Mói, Anderson Luiz Rezende (2002)
The utilization ofthe derivatives as instrument ofrisk protection has been astrategy very utilized in the commodities market. However, these markets can not only reduce the risks ofprice variation ofthe products negociated on future as generate other risk factors to the players. These new risk factors are related to the daily adjustments payed/received by the participants during the endurarice ofthe contracts. So, to know better the extension ofthe exposure to the risks generated by these daily adjustments, itwas conceived amodel to the series ofcoffee future returnings offour periods. It was made na examination of the volatility ofthe coffee returnings trhoughout the models ofthe ARCH class. The empirical data suggest strong signs ofpersistence and assymetry on the volatility ofthe series that are further away ofthe due date ofthe contract. The utilized criteria ofthe adjustment quality indicated that ali the estimated models had agood performance. The foresight ofthe VaRs ofthe daily adjustments for the periods of March and Sptember, 2002 have shown themselves very significant ifcompared with the real values at risk for these periods.